A systematic literature review on internal audit quality and job performance - Lukman, Jimoh Adams; Legodi, Audrey Hlabisang (Edelweiss Applied Science and Technology, 2026)
The study is a systematic literature review and bibliometric analysis of internal audit quality aimed at evaluating the conceptual definitions, theoretical background, and methodologies adopted in past studies. 345 records were located in various databases, of which 150 studies passed the inclusion criteria according to PRISMA guidelines. Bibliometric mapping with the help of VOSviewer identified intellectual structures, with audit quality, audit fees, corporate governance, and auditor competence as the main themes. Important aspects of internal audit quality were summarized, such as independence, competence, objectivity, due professional care, risk-based auditing, and internal control effectiveness, with inconsistency in the operationalization of these variables in the literature. Theoretical analysis revealed that agency, stewardship, institutional, and resource-based theories prevailed, and there was little adjustment to the internal audit framework; other perspectives were underrepresented. Research is methodologically dominated by cross-sectional surveys and archival studies, and rarely by longitudinal and experimental research. Results indicate that audit quality and auditor performance are bidirectional, although the causal pathways are poorly studied. The contribution of this review is that, by combining PRISMA and bibliometric analysis, the field is mapped and can be applied practically to audit committees, chief audit executives, and governance boards, and offers future research directions, especially in behavioral, technological, and emerging market environments.